Politics and Social Forces in Chilean Development - Petras, James (University of California Press, 2020)
Chile, which suffering from many of the same social and economic problems that afflict other Latin American countries, has enjoyed remarkable political stability. With the exception of one brief interlude, Chile has been governed by elected rules for half a century. The feature of Chilean development that explains its exceptional nature in contrast to the rest of Latin America is the special role of the bureaucracy, which functions as a broker for the conflict.